2020
DOI: 10.1111/php.13231
|View full text |Cite
|
Sign up to set email alerts
|

Site‐specific Bioconjugation and Convergent Click Chemistry Enhances Antibody–Chromophore Conjugate Binding Efficiency

Abstract: Photosensitizer (PS)–antibody conjugates (photoimmunoconjugates, PICs) enable cancer cell‐targeted photodynamic therapy (PDT). Nonspecific chemical bioconjugation is widely used to synthesize PICs but gives rise to several shortcomings. The conjugates are heterogeneous, and the process is not easily reproducible. Moreover, modifications at or near the binding sites alter both binding affinity and specificity. To overcome these limitations, we introduce convergent assembly of PICs via a chemo‐enzymatic site‐spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
2
14
1
Order By: Relevance
“…However, hepatic accumulation was increased twofold for the mIgG1 PD-L1-srt-his antibody compared to the other antibodies, most likely caused by the presence of the Histag [ 46 , 47 ]. Although previous studies showed that random DTPA conjugation via lysine side chains can influence affinity [ 24 ], in vivo pharmacokinetics [ 25 , 48 ] and therapeutic index [ 49 ], we did not observe differences in blood clearance or tumor uptake for site-specifically versus randomly labeled mIgG1 aPD-L1 with DTPA or IH20 . Finally, no statistical differences in biodistribution were observed for IH20 - and IH18 -conjugated chimeric mIgG1 aPD-L1, except for the spleen, where uptake of mIgG1-IH18 was significantly higher, potentially caused by the apparent higher blood concentration 24 h p.i.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…However, hepatic accumulation was increased twofold for the mIgG1 PD-L1-srt-his antibody compared to the other antibodies, most likely caused by the presence of the Histag [ 46 , 47 ]. Although previous studies showed that random DTPA conjugation via lysine side chains can influence affinity [ 24 ], in vivo pharmacokinetics [ 25 , 48 ] and therapeutic index [ 49 ], we did not observe differences in blood clearance or tumor uptake for site-specifically versus randomly labeled mIgG1 aPD-L1 with DTPA or IH20 . Finally, no statistical differences in biodistribution were observed for IH20 - and IH18 -conjugated chimeric mIgG1 aPD-L1, except for the spleen, where uptake of mIgG1-IH18 was significantly higher, potentially caused by the apparent higher blood concentration 24 h p.i.…”
Section: Discussioncontrasting
confidence: 93%
“…In most of these studies, imaging moieties were coupled to the targeting antibody using non-selective protein modification methods, without spatial control. However, such random conjugation can interfere with the antigen-binding region and consequently alter the binding affinity [ 24 ] and in vivo pharmacokinetics [ 25 , 26 ]. In contrast, site-specific labeling does not interfere with the antigen-binding site and yields a more controlled, homogeneous and therefore reproducible product.…”
Section: Introductionmentioning
confidence: 99%
“…Non-glycosylated approaches to antibody modification are not limited to toxin attachment. Other reports have detailed the attachment of azide polymers, 271 photosensitiser motifs 272 or virus nanoparticles. 273 Recent research offers some reservations concerning the selectivity of mTG for the conserved PWEEQYNST sequence (containing Q295) in the Fc region.…”
Section: Transglutaminasementioning
confidence: 99%
“…By exploiting the advantages of the photoSPAAC reaction, the labeling occurred in a one-pot reaction with only a few minutes of light exposure (Figure ). In similar applications, SPAAC photoclick reactions were employed as light-responsive photoaffinity probes for detecting carbohydrate-binding proteins and antibodies. …”
Section: Applicationsmentioning
confidence: 99%